2005
DOI: 10.1177/15910199050110s123
|View full text |Cite
|
Sign up to set email alerts
|

Brain AVM Embolization with Onyx®: Analysis of Treatment in 34 Patients

Abstract: The endovascular approach to arteriovenous malformations (AVM) using different embolizing agents is a well-established treatment option. This report assesses the results of our experience using a non “glueing” embolic material available for several years, commercially known as Onyx®. We used Onyx to treat 34 consecutive patients in the last four years. All patients were treated in the same department by the same neuroradiological team, with a strictly repetitive tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In another clinical series of 48 cases by Pierot et al, 22 the morbidity rate was 10% and the mortality rate was 2%. Leonardi et al 23 reported 3% transient morbidity and 3% mortality among 34 AVMs with S-M grades III-V. No descriptions of clinical outcomes in patients after TVEO of BAVMs were found. Significant improvements in endovascular devices and interventionalists' skills, as well as the quality of angiography suite images, have allowed venous navigation to become progressively safer and more efficient.…”
Section: Discussionmentioning
confidence: 99%
“…In another clinical series of 48 cases by Pierot et al, 22 the morbidity rate was 10% and the mortality rate was 2%. Leonardi et al 23 reported 3% transient morbidity and 3% mortality among 34 AVMs with S-M grades III-V. No descriptions of clinical outcomes in patients after TVEO of BAVMs were found. Significant improvements in endovascular devices and interventionalists' skills, as well as the quality of angiography suite images, have allowed venous navigation to become progressively safer and more efficient.…”
Section: Discussionmentioning
confidence: 99%
“…Initial experiences using the Onyx system in the endovascular treatment of cerebral AVMs has been reported in single and multicenter studies (17,18,(28)(29)(30)(31)38). The results are promising, including achievement of long-duration injections (29) and improved angiographic outcomes (28).…”
Section: Discussionmentioning
confidence: 99%
“…The results are promising, including achievement of long-duration injections (29) and improved angiographic outcomes (28). Although a good outcome could be attained in the majority of patients, a correct embolization technique is mandatory to avoid complications (18,31). Regardless, long-term monitoring of patients is mandatory, especially for patients with AVMs that have been cured by embolization alone.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical article by Pérez-Higueras et al, 14 10 totally occluded AVMs (22.2%) were reported among 45 cases. In another clinical series of 48 cases by Pierot et al, 15 2 AVMs (4.2%) were completely obliterated, whereas Leonardi et al 16 23 13 AVMs (18.6%) were completely embolized with Onyx. In another series of 94 patients, Mounayer et al 24 reported angiographic cure in 26 patients; in this series, the treatment was completed for 53 patients, by using a combination of Onyx and n-BCA.…”
Section: Discussionmentioning
confidence: 93%